PENGARUH KOMPENSASI DAN FASILITAS KERJA TERHADAP SEMANGAT KERJA - Dharma Setiawan; Helly Khairuddin; Leni Indriani (Indragiri Research Center (ingreat), 2023)
This research aims to analyze the influence of Compensation on Work Morale, analyze the influence of Work Facilities on Work Morale, analyze the influence of the Effect of Compensation and Work Facilities on Work Morale. The population of this study is all the Bagan Jaya village officials, Enok sub-district, totaling 91 people. The data collection method used was using a questionnaire. The data analysis technique uses SPSS Version 26. Based on the research results, it is concluded that there is a significant influence of compensation on the work spirit of village officials. There is a significant influence of facilities on the work morale of village officials. There is a significant influence of the work morale variable on the compensation and facilities variables.